Analisis Pengaruh Pertumbuhan Ekonomi, Jumlah Penduduk, Indeks Pembangunan Manusia, dan Tingkat Pengangguran Terbuka Terhadap Kemiskinan di Indonesia Periode 2017-2022 - Aulia, Nadia Restu; Syafitri, Annisa; Pratama, Andri Adi; Azizah, Wafidz; Fitria, Aulia Octa; Kholiq, Firman (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
This study seeks to assess the impact of economic growth, population size, Human Development Index (HDI), and open poverty rates on poverty levels in Indonesia throughout the 2017-2022 timeframe. The methodology employed involves panel data regression analysis to scrutinize the correlation between these variables and poverty levels. The outcomes of the investigation reveal that economic growth exhibits a statistically insignificant adverse influence on poverty, while the magnitude of the population does not yield a significant effect. The efficacy of HDI in mitigating poverty also demonstrates an insignificant outcome. Nonetheless, these findings offer a novel standpoint on the efficacy of policies related to human development in enhancing well-being. Additionally, it is imperative to acknowledge the impact of open poverty levels on the overall poverty scenario. In conclusion, this research contributes to understanding the dynamics of factors that influence poverty levels in Indonesia during this period, by implementing policies for poverty alleviation in the future.”